Expert Commentary to the Article of C.I. Parente, R.M. Tsipan, R.L. Hendren «Integrating Treatment for Autism: Psychiatric Comorbidities and Comprehensive Treatment - A.F. Shaposhnikova (Moscow State University of Psychology and Education, 2021)
A child psychiatrist practitioner commentary on an article «Integrating Treatment for Autism: Psychiatric Comorbidities and Comprehensive Treatment» by american clinical investigators published in the current issue of the journal. The commentary refers to the similarities and differences in the medical approaches to the treatment of autism spectrum disorders (ASD) in Russia and in the United States. The issue of the need for drug therapy in the treatment protocol for autism in childhood is specifically addressed. Differences in the clinical recommendations of psychiatrists of both countries on the use of certain antipsychotics therapy are considered. It is concluded that an integrated approach to treatment and a reasonable combination of drug and non-drug methods due to the existing gaps in understanding the etiology and pathogenesis of ASD are necessary